Applying Bayesian Belief Network to explore key determinants for nature-based solutions' acceptance of local stakeholders. (10th August 2021) - Dai, Li; Han, Qi; de Vries, Bauke; Wang, Yang
Abstract: Existing research stops short of explaining why local stakeholders have a low acceptance of nature-based solutions. In this article, the public, government, and project management perspectives are combined to examine the factors that influence nature-based solutions acceptance at the community level. Based on the survey data of 657 respondents in Guyuan, China, the study has found that government-, and project-related factors are more likely to influence the degree of community acceptance to nature-based solutions through the Bayesian Belief Network. These factors include the availability of feedback and the availability of information from the government perspective and project design and location from the project management perspective. Only one public-related factor is identified to influence community acceptance significantly, namely, personal experiences. In addition, this study found a large portion of respondents belongs to the silent majority in the survey that holds neutral views towards nature-based solutions. Finally, recommendations are given on translating the key determinants for Nature-based solutions that were found into NBS policies. Highlights: An innovative structure by revealing cause-effect relationships of local acceptance of nature-based solution (NBS) projects. A bulk of factors influence citizens' response to NBS greatly, and for a single factor, the impact is limited. A large portion of respondents with indifferent attitudes towards NBS can be grouped as the silent majority. The results provide a basis for policy-makers insight into NBS acceptance impact factors and setting strategies.